Experience report: study on mental health and use of psychotherapy medicine among medicine students in the Extreme South of Bahia (Research, Society and Development, 2023)
Introduction: Considering the high prevalence of psychiatric disorders among medical students, it is essential that educational institutions develop measures aimed at combating and preventing the development of these conditions. Objectives: To analyze mental health and the consequent use of psychotropic drugs among medical students. Methodology: Observational, cross-sectional, descriptive study, carried out through an online questionnaire, Google Forms, during the months of March and April 2023, with medical students from the Extreme South of Bahia. The students were asked about their life and health habits, as well as the use of psychotropic drugs. Results: In the experience, there was a prevalence of responses from students from private institutions, female, between 21 and 25 years old, from the 1st to the 2nd year. Most reported having increased anxiety after starting the course and, therefore, receive psychological support. Most academics practice some religious or leisure activity, prioritize rest and do not perform self-medication. When they use some psychotropic drug, emphasis is given to antidepressants and psychostimulants. Conclusion: It is essential to mobilize the academic community in an attempt to provide individual and collective support, in view of the mental illness of the studied population. The measures should highlight the risk and protective factors for the mental health of academics, faculty and student support staff, for the consequent reduction of mental disorders and the use of psychotropic drugs.